2021
DOI: 10.1177/21650799211014768
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Labor and Depressive Symptoms Among Healthcare Workers: The Role of Sleep

Abstract: Background: Depression is the second leading cause of disability worldwide. Health care workers report a higher prevalence of depressive symptoms than the general population. Emotional labor has contributed to poor health and work outcomes. However, the mechanism for the potential association between emotional labor and depressive symptoms has not been well studied. This study examines the relationship between emotional labor and depressive symptoms and whether sleep plays a role in explaining this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…It appealed that depression and anxiety prevalence among HCWs were 22.8 and 23.2%, respectively, derived from a meta-analysis including 33062 subjects (12). Meanwhile, existing literature has shown that HCWs represent the highest risk groups of depressive symptoms, suicide, and post-traumatic stress disorder (PTSD) among the general population (13)(14)(15). It leads to a high incidence of low job satisfaction, absenteeism and turnover directly (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appealed that depression and anxiety prevalence among HCWs were 22.8 and 23.2%, respectively, derived from a meta-analysis including 33062 subjects (12). Meanwhile, existing literature has shown that HCWs represent the highest risk groups of depressive symptoms, suicide, and post-traumatic stress disorder (PTSD) among the general population (13)(14)(15). It leads to a high incidence of low job satisfaction, absenteeism and turnover directly (13).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, existing literature has shown that HCWs represent the highest risk groups of depressive symptoms, suicide, and post-traumatic stress disorder (PTSD) among the general population (13)(14)(15). It leads to a high incidence of low job satisfaction, absenteeism and turnover directly (13). Hence, we should pay attention to HCWs' mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the SHIFT study, there was a statistically significant association between surface-acting emotional labor and depressive symptoms. 18 This negative effect was notable in its own right and also partially mediated through sleep disturbances.…”
Section: Preventable Risk Factors For Stress Burnout and Related Conc...mentioning
confidence: 99%
“…Stres ise kendini psikolojik, davranışsal ve fiziksel olarak farklı şekillerde göstermekte, uykusuzluk, yeme düzeninde bozukluk, sinir hali, tansiyon ve kalp rahatsızlığı gibi olumsuzluklara neden olmaktadır (Abraham, 1998:137-146). Duygusal emek ve depresif semptomlarda uykunun etkisinin araştırıldığı bir çalışmada, duygusal emek ve depresif semptomlar sergileme arasında bir ilişkinin olduğu ve uykunun bu ilişkide aracı rol üstlendiği gözlemlenmiştir (Zhang et al, 2021).…”
Section: Duygusal Emekunclassified